EVIDENCE FOR LOCAL COMPENSATION OF BARYON NUMBER IN E+E- ANNIHILATION - Althoff, M; Braunschweig, W; Kirschfink, F; Lubelsmeyer, K; Martyn, H; Rimkus, J; Rosskamp, P; Sander, H; Schmitz, D; Siebke, H; Wallraff, W; Fischer, H; et al. (1984)
We have studied at CM energies of 14, 22 and 30-36.7 GeV e+e- annihilation events in which the hadronic final state contains both a proton and an antiproton in the momentum range 1.0 < p < GeV/c. We find that such pairs are produced predominantly in the same jet and conclude that baryon-antibaryon production is dominated by a mechanism involving local compensation of baryon number. © 1984.